“This Group Is My Country”: Sri Lankan Tamil Women’s Narratives of Isolation and Connectedness in Australia - Mehta, Rimple (2022)
Refugees lose their networks and support systems on their journey from their home country. In addition, they may experience torture, trauma, and socio‐economic hardship. A critical question concerning refugee wellbeing is how refugee belonging, inclusivity, and community connectedness can be better understood, strengthened, and promoted. In this article, we discuss how members of the Tamil Seniors Group, supported by the NSW Service for the Treatment and Rehabilitation of Torture and Trauma Survivors (STARTTS), develop social networks in Australia. Based on two focus group discussions, this article analyses their experiences through the intersection of age and gender to elucidate the challenges and affordances of networking and establishing social relations in Australia.